2000
DOI: 10.1093/oxfordjournals.aje.a010124
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-Transferase Polymorphisms and Colorectal Cancer: A HuGE Review

Abstract: The genes glutathione S-transferase M1 (GSTM1) (chromosome 1p13.3) and glutathione S-transferase T1 (GSTT1) (22q11.2) code for cytosolic enzymes glutathione S-transferase (GST)-mu and GST-theta, respectively, which are involved in phase 2 metabolism. Both genes may be deleted. There is geographic and ethnic variation in genotype frequencies for both genes. In developed countries, colorectal cancer is the second most common cancer. Colorectal cancer has been inconsistently associated with polycyclic aromatic hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
190
1
8

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(215 citation statements)
references
References 0 publications
16
190
1
8
Order By: Relevance
“…The two GST isoforms GST M1 and GST T1 are subjects to genetic polymorphisms, and geographic as well as ethnic variations in genotype frequencies are known for both genes. Indeed, GSTl polymorphism has been implicated as a variable, which determines the protective effect of broccoli against the development of precancerous adenomatous polyps in human populations [208]. In a recent epidemiological study, Lin et al [209] observed a protective effect of broccoli consumption against adenomatous polyps only in subjects with the GSTM1 null genotype because ITCs are conjugated and excreted more slowly in subjects who do not express GSTl, so that exposure of target tissues to the protective compound and/or metabolite is higher and prolonged.…”
Section: Effect Of Genetic Polymorphisms On Gls Metabolism and Interimentioning
confidence: 99%
“…The two GST isoforms GST M1 and GST T1 are subjects to genetic polymorphisms, and geographic as well as ethnic variations in genotype frequencies are known for both genes. Indeed, GSTl polymorphism has been implicated as a variable, which determines the protective effect of broccoli against the development of precancerous adenomatous polyps in human populations [208]. In a recent epidemiological study, Lin et al [209] observed a protective effect of broccoli consumption against adenomatous polyps only in subjects with the GSTM1 null genotype because ITCs are conjugated and excreted more slowly in subjects who do not express GSTl, so that exposure of target tissues to the protective compound and/or metabolite is higher and prolonged.…”
Section: Effect Of Genetic Polymorphisms On Gls Metabolism and Interimentioning
confidence: 99%
“…A recurrent problem in case-control studies of gene disease associations with unrelated controls has been that the controls were not selected from the same source population as the cases (10,(34)(35)(36). The potential problem of selecting controls who do not represent the population from which cases arise is illustrated by the divergence in odds ratios for the association between colorectal cancer and the glutathione S-transferase T1 gene (GSTT1) null genotype (37), when the different control groups were analyzed (36).…”
Section: Selection Of Subjectsmentioning
confidence: 99%
“…The potential problem of selecting controls who do not represent the population from which cases arise is illustrated by the divergence in odds ratios for the association between colorectal cancer and the glutathione S-transferase T1 gene (GSTT1) null genotype (37), when the different control groups were analyzed (36). Thus, sufficient information should be presented to assess whether controls would have become cases if they had developed the disease.…”
Section: Selection Of Subjectsmentioning
confidence: 99%
“…However, a measure of relevant exposures is not always performed. A recent review of GSTM and GSTT polymorphisms and colorectal cancer 14 reported on 9 studies, 5 of which had no exposure assessment.…”
Section: Discussionmentioning
confidence: 99%